Pharmaceutical Companies & Liquidity Analysis: A Review - Saini, Neetu; Bansal, Sanjeev (International Journal of Economics and Financial Issues, 2020)
Liquidity is a vital character in the thriving performance of the business firm. A firm should make sure that it does not undergo from being short of or surplus liquidity position for the smooth running of the business operations. The predominant part in administration of working funds of a company is maintaining its liquidity, so that day-to-day operations and its obligations can be met. Hence, it is of greatest significance to maintain a steady look at liquidity position of the business as without it the company cannot survive. The current manuscript aims to study the liquidity position of the ten selected pharmaceutical companies by analyzing various liquidity ratio such as current ratio and quick ratio for the period 2004-2013. Short term creditors are mainly involved in the liquidity position of the firms to recognize the alacrity of business to oblige its current liabilities. Keywords: Liquidity, ratios, pharmaceutical. JEL Classifications: G23, G33 DOI: https://doi.org/10.32479/ijefi.10465